Antimicrobial and antioxidant potentials of essential oil and acetone extract of Myristica fragrans Houtt. (aril part) - Singh, Gurdip (2005)
The antifungal, antibacterial, and antioxidant potentials of essential oil and acetone extract were carried out by different techniques. In poison food medium method, the essential oil showed complete zones of inhibition against Fusarium graminearum at the all tested doses. For other tested fungi and bacteria, they gave good to moderate zone inhibition. The antioxidant activity was evaluated by measuring peroxide, thiobarbituric acid and total carbonyl values of rapeseed oil at fixed time intervals. Both the extract and essential oil showed strong antioxidant activity in comparison with butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT). In addition, their inhibitory action in linoleic acid system was studied by monitoring peroxide concentration in emulsion during incubation. The results were well correlated with above values. Their radical scavenging capacity was carried out on 2,2′-diphenyl-1-picrylhydracyl (DPPH) radicalm, and they showed strong scavenging activity in comparison with synthetic antioxidants. Their reducing power was also determined, which also proved strong antioxidant capacity of essential oil and extract. Gas chromatographic-mass spectroscopy studies on essential oil resulted in the identification of 49 components representing 96.49% of the total amount, and the major component was sabinene (20.22%), followed by terpinen-4-ol (12.08%), safrole (10.32%), α-pinene (9.7%), β-phellandrene (6.56%), and γ-terpinene (5.93%). The acetone extract showed the presence of 23 components representing 71.66% of the total amount. The major components were isocroweacin (18.92%), elemicin (17.68%), methoxyeugenol (8.13%), linoleic acid (4.12%), dehydrodiisoeugenol (4.06%), palmitic acid (2.8%), and trans-isoeugenol (2.76%). © 2005 Institute of Food Technologists.